Fumigant toxicity of four essential oils against the carob moth Ectomyelois ceratoniae Zeller and the Mediterranean flour moth Ephestia kuehniella. - Chaaban, Samah Ben; Haouel-Hamdi, Soumaya; Bachrouch, Olfa; Mahjoubi, Kamel; Mediouni Ben Jemâa, Jouda (International Journal of Environmental Health Research, 2024)
Eucalyptus leucoxylon, Rosmarinus officinalis, berries, and leaves of Schinus molle essential oils were analysed using GC-MS techniques and assessed for their fumigant toxicity against adults, larvae, and eggs of Ectomyelois ceratoniae and Ephestia kuehniella. Results showed that E. leucoxylon contained Spathulenol, p-Cymene, and Cryptone as major compounds. GC – MS analyses showed that the major compounds of R. officinalis essential oil were 1,8-Cineole, Camphor, and α-pinene. I-Phellandrene, t-Muurolol, and Phellandrene were the major components of the S. molle leaves; while I-Phellandrene, Limonen, and δ-Cadinene were the major components of the S. molle berries. S. molle berries were the most efficient followed by R. officinalis against E. ceratoniae and E. kuehniella. The most effective tested essential oil against E. ceratoniae larvae was S. molle berries. Results on the ovicidal and larvicidal effects of the tested oils demonstrated that R. officinalis was the most effective essential oil against E. kuehniella eggs.